2014
DOI: 10.1258/phleb.2012.012073
|View full text |Cite
|
Sign up to set email alerts
|

Use of impedance ratios to assess hand swelling in lymphoedema

Abstract: Bioimpedance spectroscopy is a promising tool for the detection of secondary hand lymphoedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“… 41 Concurrent validity has been studied using a variety of assessment methods involving both clinical and research models of BIA devices. Moderate to strong correlations have been reported between BIA data and both self-report ( r = .71, research model 46 ) and perometry results ( r = .71-.93, research model 34 , 42 , 43 , 47 ; r = .40-.60, clinical model 48 ). Correlation with circumferential measurement ranged from low (clinical model) 49 to moderate (.31-.52, research model, 50 clinical model 41 ).…”
Section: Bioimpedance Analysismentioning
confidence: 99%
“… 41 Concurrent validity has been studied using a variety of assessment methods involving both clinical and research models of BIA devices. Moderate to strong correlations have been reported between BIA data and both self-report ( r = .71, research model 46 ) and perometry results ( r = .71-.93, research model 34 , 42 , 43 , 47 ; r = .40-.60, clinical model 48 ). Correlation with circumferential measurement ranged from low (clinical model) 49 to moderate (.31-.52, research model, 50 clinical model 41 ).…”
Section: Bioimpedance Analysismentioning
confidence: 99%
“…Bioelectrical impedance analysis enables the identification of body liquids, the determination of edema in the trunk and limbs, and the monitoring of the dynamics of body liquids over time [9][10][11]. Normally, the lower limbs and the arm with lymphedema are the first to swell.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring electrodes were placed over the third MCP joint and ulnar styloid for the measurement of the hand. 18 For arm Seg A, the two measurement electrodes were positioned at the ulnar styloid and 10 cm proximal to the ulnar styoid. The measurement electrodes were then systematically moved 10 cm proximally until all four segments had been measured.…”
Section: Assessmentsmentioning
confidence: 99%
“…16,17 Exploratory studies using BIS have demonstrated that BIS is sufficiently sensitive to measure impedance over smaller distances, including 10 cm-segments in the arm 14 and the dorsum of the hand. 18 However, the thresholds for these shorter segments have not been determined.…”
Section: Introductionmentioning
confidence: 99%